Random Votes to Parties and Policies in Coalition Governments - Cervellati, Matteo; Gulino, Giorgio; Roberti, Paolo (Econometrica, 2024)
We exploit a natural experiment involving a randomization of votes across parties within coalitions in all local elections in Italy for over a decade. A lottery on the position of party symbols in the ballot papers allows estimating the causal effect of increasing votes to parties for coalition policies. A non‐marginal random boost of votes shifts budgetary spending towards the treated party's platform, but only for issues that are salient in that party's political manifesto. We study the chains of mechanisms mapping votes into policies and link it to an increase in bargaining power within legislative majorities. Parties leverage their higher electoral support to gain the appointment of politically affiliated cabinet members. Empowering different parties also leads to the selection of cabinets with different socio‐demographic characteristics. The unintentional experiment helps shed new light on mechanisms mapping votes to parties into coalition policies.